PEMBERIAN ABU VULKANIK TERHADAP PERTUMBUHAN KELAPA SAWIT (Elaeis guineensis Jacq.) DI MAIN NURSERY - Ryan Qomar Alviandy; Erlida Ariani; Sukemi Indra Saputra (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The research aimed to determine the effect of volcanic ash and get the best treatment to the growth of palm oil (Elaeis guineensis Jacq.) seedlings in main nursery. The research was conducted at the experimental field of the Faculty of Agriculture, University of Riau. This research was conducted from March to August 2015. The research used Completely Randomized Design consisting of 5 treatments with 3 replicates that contained 15 experimental units. Each unit consist of 2 seeds, so the total crop was 30 plants. Parameters measured were the increase seedling height, the number of leaves increase and the increase hump diameter. Data were analyzed by analysis of variance and further tested using Duncan`s New Multiple Range Test at the level of 5%. The results of the research showed that significantly affects the volcanic ash on increase of seedling height and seedling hump diameter. The treatment of ash volcanic 100 g/plant gives the best seedling growth of all observed parameters in main nursery. Keywords: palm oil, growth, volcanic ash